Romances rebeldes - a tradição de rebeldia na literatura norte-americana: de Moby Dick a On the Road - Santos, Renato Alessandro dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
It is possible to identify in American Literature the existence of a tradition of resistance and rebellion that begins in the 19th century with Henry David Thoreau and extends throughout the 20th century. That tradition includes works in prose and verse that express artistic, cultural and social discontent and that criticize modern civilization, often employing the theme of travelling and portraying incidents in the lives of characters who are always on the move. Using and questioning the concept of tradition as expressed by T.S. Eliot, Octavio Paz and Robert Spiller, in the light of what we call a tradition of rebellion, this thesis analyses, six novels of that tradition: Herman Melville's Moby Dick, Mark Twain's The Adventures of Tom Sawyer and The Adventures of Huckleberry Finn, Jack London's Call of the Wild, Ernest Hemingway's The Sun Also Rises and Jack Kerouac's On the Road

Na literatura norte-americana, é possível confirmar a existência de uma tradição de rebeldia que se inicia no século 19 com Henry David Thoreau (1817-1862) e que se estende por todo o século 20. São obras em prosa e verso que se valem da liberdade de expressão para manifestar inconformismo artístico, cultural, político e social, bem como para criticar a civilização moderna, abordando o tema da viagem e retratando a experiência vivenciada por personagens sempre em movimento. Usando e problematizando o conceito de tradição como expresso por T.S. Eliot (1888-1965), Octavio Paz (1914-1998) e Robert E. Spiller (1896-1988), este trabalho analisa, à luz do que chamamos tradição de rebeldia, seis romances dessa tradição: Moby Dick (1851), de Herman Melville (1819-1891); As aventuras de Tom Sawyer (1876) e As aventuras de Huckleberry Finn (1884), ambos de Mark Twain (1835-1910); Chamado selvagem (1903), de Jack London (1876-1916); O sol também se levanta (1926), de Ernest Hemingway (1899-1961), e On the Road (1957), de Jack Kerouac (1922-1969)
Keywords: Literatura; Literatura - História e crítica; Literatura americana; Ficção; Literature